The Impact of the Job Creation Law and Other Variables on Indonesia's FDI from 2018 to 2024 - Sofiana, Apriani; Sohibien, Gama Putra Danu (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Although national Foreign Direct Investment (FDI) realization in Indonesia increased following the enactment of the Job Creation Law in 2021, regional FDI realization actually showed a decline in 17 of Indonesia's 34 provinces. Reviews from international organizations such as the World Bank and the World Trade Organization (WTO) suggest the need for analysis to examine the influence of investment-supporting variables on FDI in Indonesia, including the Job Creation Law policy. Therefore, the objective of this study is to analyze the variables influencing regional FDI realization in 34 provinces for the 2018-2024 period. The method used is panel data regression with the selected Random Effect Model (REM). The results show that the Household Consumption Expenditure (HCE) as a proxy for market size, non-oil and gas exports as a proxy for openness of market access, the mining sector's GRDP as a proxy for natural resource potential, and the Job Creation Law have a positive effect on regional FDI realization. These results align with eclectic dunning theory. Disparities in FDI realization were also found, regions outside Java Island that experienced high FDI realization were partly due to internal factors such as abundant natural resources, the presence of industrial areas, and product diversification.